2018
DOI: 10.2903/sp.efsa.2018.en-1493
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of in silico tools for the prediction of dermal absorption for pesticides

Abstract: Based on the “Human in vitro dermal absorption datasets” published as supporting information to the revised EFSA Guidance on Dermal Absorption, in silico models for prediction of absorption across the skin have been evaluated. For this evaluation, a systematic literature search and review was performed, identifying 288 publications describing mathematical models for prediction of dermal absorption. Eleven models potentially relevant to the regulatory assessment of pesticides and which cover a range of approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Kneuer et al [ 22 ] investigated available in silico models for the prediction of absorption across the skin. For this, suitable models potentially relevant to the regulatory assessment of pesticides were selected from the literature to compare predicted dermal absorption values versus measured data of plant protection products using a large dataset of in vitro dermal absorption studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kneuer et al [ 22 ] investigated available in silico models for the prediction of absorption across the skin. For this, suitable models potentially relevant to the regulatory assessment of pesticides were selected from the literature to compare predicted dermal absorption values versus measured data of plant protection products using a large dataset of in vitro dermal absorption studies.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the specific combination of co-formulants was not part of the selected models. Kneuer et al [ 22 ] highlighted that one model is worthy for further investigations to estimate the dermal absorption value in the absence of adequate experimental data, but it was noted that the influence of physico-chemical properties had to be investigated further. Furthermore, none of the selected models took into account the possible co-formulant’s effect on the stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent, European Food Safety Authority (EFSA) projects on in silico methods for evaluating dermal absorption of pesticides and protein toxicity confirmed that the computational approach has been widely accepted. 8 In parallel to this, the recent development of systems biology and multiscale modelling has increased the understanding of the physiological endogenous pathway and effects of toxicants on the temporal behaviour of the cell, tissue, and whole-organ systems.…”
mentioning
confidence: 99%